2019
DOI: 10.11113/jt.v81.12566
|View full text |Cite
|
Sign up to set email alerts
|

Climatological Calibration of Z-R Relationship for Pahang River Basin

Abstract: Flood disaster due to prolonged heavy rainfall had caused millions ringgit of property losses, infrastructure damages and numerous deaths in the east coast region of Peninsular Malaysia. One of the efforts taken to improve disaster preparedness in this region is by enhancing the flood forecasting and warning system (FFWS) using rainfall input from weather radar. Weather radar has the advantage of its ability to provide good spatial and temporal resolution of rainfall estimates but comes with inherent associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Figure 9 provides the bar graph of areal rainfall comparison which shows higher radar QPE values during certain event as compared to the gauged rainfall. The findings are different from other studies done in the country where the radar QPE had underestimated the gauged rainfall [14,15].…”
Section: Overall Performancecontrasting
confidence: 99%
See 2 more Smart Citations
“…Figure 9 provides the bar graph of areal rainfall comparison which shows higher radar QPE values during certain event as compared to the gauged rainfall. The findings are different from other studies done in the country where the radar QPE had underestimated the gauged rainfall [14,15].…”
Section: Overall Performancecontrasting
confidence: 99%
“…This situation can influence the correlation and estimation accuracy of radar rainfall estimates, thus increasing errors as the distance from radar increases. Studies by [14,15,22] also found that the inaccuracy of radar rainfall estimates increase as it gets further away from the radar. Figure 7 shows the scatter plots of radar QPE versus gauged rainfall for each rainfall station with lines of discrepancy ratio (DR).…”
Section: Overall Performancementioning
confidence: 97%
See 1 more Smart Citation
“…In the past, it has been common to use Marshall and Palmer Z-R relationship for all categories of rain. However, many studies have demonstrated that parameters 𝑎 varies widely according to region and much lower values are identified as suitable for use especially in tropical region [4][5][6][7][8]. Since Malaysia is one of the tropical countries that experience heavy rainfall rate throughout the year, the selection of suitable Z-R relationship is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Mean Field Bias (MFB) merging technique will be employed in this study using static and dynamic calibration steps to improve the radar QPEs. An innovation in this study compared to the previous studies for NaFFWS project is the use of composite radars for the generation of QPEs instead of a single radar as the data source for QPE derivation [16], [17].…”
mentioning
confidence: 99%